Fatores associados a sintomas depressivos em mães de recém-nascidos pré-termos de muito baixo peso - Prado, Marília Martins (2013)
The survival of newborn preterm and very low birth weight (VLBW) infants has increased in recent decades and preterm delivery has been touted as a stressor in relation to maternal emotional balance. Mothers of VLBW have higher incidence of anxiety and depressive symptoms, as well as poorer perception of well-being than mothers of full-term newborns. This study examined the intensity of depressive symptoms in mothers of VLBW infants during the initial 12 months after childbirth and the association of these symptoms with sociodemographic characteristics, maternal quality of life and infants clinical characteristics. Mothers of VLBW infants (gestational age ≤ 34 weeks; birth weight < 1.500 g) admitted to a neonatal intensive care unit (NICU) were invited to participate in a longitudinal study. Mothers responded to the Beck Depression Inventory (BDI) and WHOQOL-BREF four times over 12 months to assess the presence and intensity of depressive symptoms and quality of life, respectively. At mother s discharge, 83 mothers participated, and then, 60, 56 and 40 mothers were interviewed after three, six and 12 months post-delivery, respectively. The BDI (median; P25-P75) scores were higher at discharge (9.0; 6-19) compared to those obtained three (6.0; 3.0-12.0) (p = 0.02), six (6.0; 2.0-10.0) (p < 0.01) and 12 months (5.0; 3.7-11.2) (p < 0.01) post-delivery (p < 0.05). An association was observed between the BDI scores and the absence of a stable marital status, many previous fetal or postnatal losses, a lower total WHOQOL-BREF score, a longer infants length of hospital stay and the presence of bronchopulmonary dysplasia (BPD). Mothers of VLBW infants, particularly single women, had more intense depressive symptoms at the time of their discharge and were more vulnerable to negative effects on their quality of life.